Methotrexate inhibits SARS‐CoV‐2 virus replication "in vitro". Issue 3 (28th September 2020) - Caruso, Arnaldo; Caccuri, Francesca; Bugatti, Antonella; Zani, Alberto; Vanoni, Marco; Bonfanti, Paolo; Cazzaniga, Marina E.; Perno, Carlo F.; Messa, Cristina; Alberghina, Lilia
Abstract: In early 2020 the new respiratory syndrome COVID‐19 (caused by the zoonotic SARS‐CoV‐2 virus) spread like a pandemic, starting from Wuhan, China, causing severe economic depression. Despite some advances in drug treatments of medical complications in the later stages of the disease, the pandemic's death toll is tragic, as no vaccine or specific antiviral treatment is currently available. By using a systems approach, we identify the host‐encoded pathway, which provides ribonucleotides to viral RNA synthesis, as a possible target. We show that methotrexate, an FDA‐approved inhibitor of purine biosynthesis, potently inhibits viral RNA replication, viral protein synthesis, and virus release. The effective antiviral methotrexate concentrations are similar to those used for established human therapies using the same drug. Methotrexate should be most effective in patients at the earliest appearance of symptoms to effectively prevent viral replication, diffusion of the infection, and possibly fatal complications. Highlights: The COVID‐19 pandemic caused by the SARS‐CoV‐2 virus is a global public health threat causing over 800000 deaths, millions of infected people, and severe economic depression. No vaccine or specific antiviral treatments are currently available. By inhibiting the host‐encoded pathway, which provides ribonucleotides to viral RNA synthesis, the FDA‐approved drug methotrexate efficiently blocks SARS‐CoV‐2 replication.